2020
DOI: 10.1186/s41235-020-00252-3
|View full text |Cite
|
Sign up to set email alerts
|

Reliance on emotion promotes belief in fake news

Abstract: What is the role of emotion in susceptibility to believing fake news? Prior work on the psychology of misinformation has focused primarily on the extent to which reason and deliberation hinder versus help the formation of accurate beliefs. Several studies have suggested that people who engage in more reasoning are less likely to fall for fake news. However, the role of reliance on emotion in belief in fake news remains unclear. To shed light on this issue, we explored the relationship between experiencing spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
208
3
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(227 citation statements)
references
References 80 publications
10
208
3
6
Order By: Relevance
“…Much like the studies reviewed above, experiments by Martel et al [48] and Bago et al [43] challenged the motivated reasoning argument as applied to fake news detection, focusing instead on the classical reasoning explanation: the more analytic the reasoning, the higher the likelihood to accurately detect false headlines. In contrast to the above accounts, both studies investigate the momentary conditions, rather than stable cognitive features, as sources of variation in fake news detection accuracy.…”
Section: Individual-level Factorsmentioning
confidence: 99%
“…Much like the studies reviewed above, experiments by Martel et al [48] and Bago et al [43] challenged the motivated reasoning argument as applied to fake news detection, focusing instead on the classical reasoning explanation: the more analytic the reasoning, the higher the likelihood to accurately detect false headlines. In contrast to the above accounts, both studies investigate the momentary conditions, rather than stable cognitive features, as sources of variation in fake news detection accuracy.…”
Section: Individual-level Factorsmentioning
confidence: 99%
“…The role of analytic reasoning and deliberation may also offer hints as to who is particularly susceptible to false information. For instance, it is possible that users who rely more on reason than on emotions when making decisions may be less vulnerable to fake news; indeed, there is some evidence that is consistent with this possibility (Martel et al, 2020).…”
Section: Floodingmentioning
confidence: 99%
“…Similarly, negative mood increased, while positive mood decreased, skepticism, deception (lie) detection, and ambiguity (Matovic, Koch, & Forgas, 2014;but see LaTour & LaTour, 2009). To date only one study examined the role of mood on news veracity detection and found that heightened emotionality predicted reduced detection of fake (but not real) news in adults (mean age 36 years) ) (Martel, Pennycook, & Rand, 2020).…”
Section: Moodmentioning
confidence: 99%